Effect of Lactobacillus casei fermented milk on fracture healing in osteoporotic mice - Guo, Xing; Zhong, Kai; Zou, LongFei; Xue, Hao; Zheng, ShuLing; Guo, Jiang; Lv, Hui; Duan, Ke; Huang, DengHua; Tan, MeiYun (Frontiers in Endocrinology, 2022)
The interaction between the gut microbiota and the host has been described experimentally by germ-free animals or by antibiotic-disturbed gut microbiota. Studies on germ-free mice have shown that gut microbiota is critical for bone growth and development in mice, emphasizing that microbiota dysbiosis may interfere with normal bone development processes. This study aimed to clarify the effect of antibiotic treatment on disturbed gut microbiota on bone development in mice and to investigate the effect of probiotic treatment on fracture healing in mice with dysbiosis. Our results showed that 4 weeks old female Kunming mice showed significantly lower abundance and diversity of the gut microbiota and significantly lower bone mineral density after 12 weeks of antibiotic treatment and significantly increased levels of RANKL and Ang II in serum (p<0.05). Mice with dysbiosis received 5 mL of Lactobacillus casei fermented milk by daily gavage after internal fixation of femoral fractures, and postoperative fracture healing was evaluated by X-ray, micro-CT scan, and HE staining, which showed faster growth of the broken ends of the femur and the presence of more callus. Serological tests showed decreased levels of RANKL and Ang II (p<0.05). Similarly, immunohistochemical results also showed increased expression of α smooth muscle actin in callus tissue. These results suggest that oral antibiotics can lead to dysbiosis of the gut microbiota in mice, which in turn leads to the development of osteoporosis. In contrast, probiotic treatment promoted fracture healing in osteoporotic mice after dysbiosis, and the probiotic effect on fracture healing may be produced by inhibiting the RAS/RANKL/RANK pathway.